Anugerah yang Terbatas? Memahami Penerimaan Remaja Akhir di Jemaat GKE Eppata terkait Kelompok Lesbian dan Homoseksual dari Teks Roma 1:26-32 menurut Kritik Respons Pembaca - Enta Malasinta Lantigimo; Lia Afriliani; Ripaldi (Jurnal Teologi Pambelum, 2023)
A different sexual orientation from heterosexual is often seen as an aberration, even in the Christianity the perpetrators are often judged as sinners. This opinion is strengthened by the support of Bible verses. One of the passages of the Bible that is often used to judge lesbians and homosexuals is the Text of Romans 1:26-32. This paper aims to examine the response in the form of understanding and acceptance by youth in the Youth Services Section of the GKE Eppata Banjarmasin Congregation regarding this biblical text and its relation to lesbian and homosexual. The method used is Reader-Response Criticism which aims to explore the meaning of the text not only from within the text itself, but from the reader. The reader has an important role in giving the meaning of a text. From the results of the Focus Group Discussion (FGD) it can be concluded that although there are various responses between those who accept and reject the existence of lesbians and homosexuals, all agree that God's grace is unlimited and applies to them as well.